Producing Litchi in Mauritius - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Producing Litchi in Mauritius 1998, 62 pp. Agricultural Research & Extension Unit Food and Agricultural Council Réduit, Mauritius. Fax: +230 464 8809 Email: areu@bow.intnet.mu http://www.agricta.org/Spore/spore77 Price per copy (inclusive of air ch